Media framing reports on Malaysia's Anti-Fake News Law - Wan, Chen (2022)
Malaysia is a democratic country that has practised Development Journalism since it gained independence from the British. The main concept of Development Journalism aims to serve the Malaysian government by promoting policies of national development on mass media. However, the freedom of media is monitored by the Malaysian government through several laws with overlapping legal provisions to regulate fake news dissemination. A more robust Anti-Fake News Law was introduced right before the 14th general election in 2018 to combat fake news. This law was disapproved by the public and media practitioners because of the severe encroachment on the rights of free speech and reporting. Thus, the main objective of this study is to investigate how Malaysian journalists frame their news reports on the Anti-Fake News Law. Framing theory differentiates the new frames as issue-specific frames and generic frames. This study used generic frames in content analysis to identify the differences between serious newspapers and tabloids. The serious newspapers include Bernama and New Straits Times, and the tabloids include The Sun and The Malay Mail. There was a total of 212 news reports from four newspapers retrieved from LexisNexis. Results show that the conflict frame was the most prevalent in the news reports covering Anti-Fake News Law, and the negative tone was the most frequently used compared to others. The results suggested that serious newspapers were found to use attribution of responsibility frames more frequently compared to tabloids, which tended to use human interest frames more frequently. The study also found that the attribution of responsibility frame was more susceptible to the positive tone whereas the conflict frame was more susceptible to the negative tone. In conclusion, Malaysia’s journalistic role performance was interfered with by the government’s agenda of national building, journalists tended to report political issues by using a more negative narrative against the practice of Development Journalism.